THE USAGE OF APHORISMS IN ENGLISH LESSONS - Musaeva G. I. (Journals Park Publishing, 2024)
This scientific article explores the utilization of aphorisms in English language lessons and their impact on learning outcomes and language proficiency. Aphorisms, concise and memorable statements that convey wisdom or general truths, have been used across various disciplines to encapsulate valuable insights. This article aims to examine the benefits of incorporating aphorisms into English language instruction, explore effective strategies for their implementation, and discuss the potential challenges and considerations for educators.
Keywords: Aphorisms, English language, subsystem, meanings, teaching methods, translation difficulties, vocabulary expansion, lesson plans.